If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 2x * -3 + -2 Reorder the terms: -3 + 4x = 2x * -3 + -2 Reorder the terms for easier multiplication: -3 + 4x = 2 * -3x + -2 Multiply 2 * -3 -3 + 4x = -6x + -2 Reorder the terms: -3 + 4x = -2 + -6x Solving -3 + 4x = -2 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -3 + 4x + 6x = -2 + -6x + 6x Combine like terms: 4x + 6x = 10x -3 + 10x = -2 + -6x + 6x Combine like terms: -6x + 6x = 0 -3 + 10x = -2 + 0 -3 + 10x = -2 Add '3' to each side of the equation. -3 + 3 + 10x = -2 + 3 Combine like terms: -3 + 3 = 0 0 + 10x = -2 + 3 10x = -2 + 3 Combine like terms: -2 + 3 = 1 10x = 1 Divide each side by '10'. x = 0.1 Simplifying x = 0.1
| 3*2x-5=2x-7 | | 2x*2+3x=2*4x-3 | | 10xy*4y= | | 2*4-5x=7-3x-4 | | 2x+x=-20x | | 2x+3-4-3x=x-2+2x | | 3(2y-4)=2(1-5y)+11 | | 7x-2+5-2x=x-2x-9 | | 2(X)+2x=-20x | | 2x-4+3x=-2-3x+6 | | (x+31)+(4x+9)=70 | | (8-y)(4y-7)=0 | | 0.3(2x-7)=0.7(9-x) | | (2x+15)+(x-30)=123 | | -6(x-4)-10=-12 | | (-4x+40)+(x+50)=180 | | x/7=-7 | | m^2+2m+3=0 | | 6x+(x+5)=180 | | x/7=-6 | | 4x-12=2x+20 | | (2x+3)+(3x-223)=180 | | 2x+40-5x=3-7x+5 | | (50-2x)(30-2x)=200 | | (2x+10)+(-x+55)=90 | | (4x+34)+(x+36)=90 | | 8(x+1)=4x+-8 | | 12c^2+15c^3= | | x^2+27x+176=0 | | 3y+4y=27 | | 568710+2= | | 3c+-1=9+t |